Manajemen dan Sejarah Pengelolaan Taman Wisata Bantimurung di Kabupaten Maros Sulawesi Selatan - I Nyoman Siryayasa; Muh. Zainuddin Badollahi; Rifal Rifal (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
This research tries to explain the development of Bantimurung Tourism Park. So the uniqueness of the Bantimurung-Bulusaraung National Park that attracts local and foreign tourists, karst: caves with beautiful stalagmites and stalagmites, and is best known as a butterfly. The method used in this study is a research method by collecting data (heuristics) that contains both primary and secondary sources obtained from interviews and the results of the presentation of previous studies, after which an assessment of the sources obtained in order to obtain information that is acceptable and reliable. The data that has been processed are then interpreted into historical narratives, after which they are written in historiography. The results of this study describe Bantimurung which has the potential of natural charm, benefits, and educational value. This development certainly has a significant impact on the economic and socio-cultural community.